THE INFLUENCE OF SEED PLANTING DEPTH AND PLANTING MEDIA COMPOSITION ON COCOA SEEDLING GROWTH: PENGARUH KEDALAMAN TANAM BENIH DAN KOMPOSISI MEDIATANAM TERHADAP PERTUMBUHAN BIBIT KAKAO - Elviani; Wilis, Ruhalena; Farida, Nurlia (PT. ROCE WISDOM ACEH, 2024)
This research aims to determine the depth of seed planting and the appropriate composition of planting media as well as the interaction between these two factors on the growth of cocoa seedlings. The research was carried out at the experimental garden of the Faculty of Agriculture, Iskandar Muda Surien University, Banda Aceh, from October to December 2023. This research used a randomized block design with a 3*3 factorial pattern with three replications to obtain 27 experimental units. There were two factors studied, namely: seed planting depth (2, 4, and 6 cm) and the composition of the manure: soil planting medium (1: 1; 1:2; 1:3). The parameters observed were seedling height and stem base diameter at 45, 60, 75 days after planting, and number of leaves at 75 days after planting. The results showed that the depth of seed planting was very significantly different from the height of seedlings aged 45, 60 and 75 dap, but was not significantly different from the diameter of the stem base aged 45, 60, 75 dap and the number of leaves aged 75 dap. The composition of the planting media was not significantly different for seed height and stem base diameter at 45, 60, 75 days after planting and the number of leaves at 75 days after planting. There was a real interaction between the depth of seed planting and the composition of the planting media on the height of cocoa seedlings at 75 days after planting.